Private sector profitability of maize production in the bajío region of guanajuato, mexico / rentabilidad privada de la producción de maíz en la región bajío de guanajuato, méxico (2014)
Abstract. Agriculture, generally speaking, is the basis of thefood system of any country. Mexico’s maize crop is particularly important, not only in terms of food security but also as in terms of culture and identity. The fact that, in recent decades, Mexico has positioned itself as the second largest importer of maize is worrying. For the purpose of measuring the private sector profitability of maize production in the Bajío region of Guanajuato, this study analyzed data from 2,996 producers who participate in the “High Yield Maize Assessment Program (PROEMAR)”, of the Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias- Bajío Experiment Camp (INIFAP-CEBAJ). We used the Policy Analysis Matrix (PAM) developed in 1989 by Monke andPearson. The results indicate that the benefit-cost ratios of the three technological systems analyzed (considering in their total income, the sale of grain and sub products), were 2.20 for rainfall (T); 1.50 for irrigation with livestock (RCA) and 1.01 for irrigation without livestock (RSA), excluding land costs; including land costs decreased the ratios to 2.13, 1.35 and 0.91. The private cost ratio (RCP), excluding the land, by production system was: T = 0.04, RCA = 0.13 and RSA = 0.85, which implies that the maize producers in the Bajío region of Guanajuato are competitive. When includingland rent in the production costs, the rainfall and irrigation with livestock systems remained competitive with a RCP of 0.07 and 0.32, respectively; not so for the production unit with the irrigation system without livestock (2.04). The most significant input was fertilizer costs, which represented 50% of the costs. / Resumen. La agricultura en general es la base del sistema alimentario de cualquier país. En México el cultivo de maíz es de especial importancia, no solo en términos de seguridad alimentaria sino también como parte de su cultura e identidad. El hecho de que durante las últimas décadas México se ha posicionado como el segundo importador de maíz a nivel mundial, resulta preocupante. Con el propósito de medir la rentabilidad privada de la producción de maíz en el Bajío de Guanajuato, se analizaron los datos de 2,996 productores que participan en el “Programa de Evaluación de Maíz de Alto Rendimiento (PROEMAR)”, del Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias-Campo Experimental Bajío (INIFAP-CEBAJ). Se usó la Matriz de Análisis de Política (MAP) desarrollada en 1989 por Monke y Pearson. Los resultados indican, que las relaciones beneficio-costo de los tres sistemas tecnológicos analizados (considerando en su ingreso total tanto la venta del grano como desubproductos), fueron de 2,20 en temporal (T); 1,50 en riego con actividad pecuaria (RCA) y 1,01 en riego sin actividad pecuaria (RSA), esto excluyendo la tierra de los costos de producción, mientras que incluyendo la tierra la relación disminuye a 2,13, 1,35 y 0,91. La relación del costo privado (RCP) excluyendo la tierra por tecnología fue: T=0,04, RCA=0,13 y RSA=0,85, lo que implica que el productor de maíz en la región Bajío de Guanajuato es competitivo. Al incluir la renta de la tierra en los costos de producción, los sistemas de temporal y riego con actividad pecuaria siguen siendo competitivos con una RCP de 0,07 y 0,32, respectivamente; no así la unidad de producción bajo el sistema de riego sin actividad pecuaria (2,04). El insumo con mayor importancia en los costos fueron los fertilizantes representando un 50 % de los costos.